O ensino remoto emergencial na unesp devido à pandemia de covid-19: uma análise baseada na percepção estudantil - Gonçalves, Taciano Moreira (2021)
With the advancement of the Covid-19 pandemic around the world, its negative impacts have been increasingly evident. As a consequence, there was a temporary closure of educational institutions in many countries, including Brazil. With the presented scenario, it was necessary to seek strategies for the continuity of the educational process. Thus, Emergency Remote Education, through the use of digital tools, has been presented as one of the alternatives used for the development of educational actions during the period of isolation. Therefore, this study aims to analyze the perception of students of college education courses on different campuses at Universidade Estadual Paulista - Unesp regarding the use of digital tools applied remotely in an emergency during the period of social distance, as well as the possible impacts on perception of learning. An analytical quantitative research, of a descriptive nature, was adopted as a methodological instrument through the application of a questionnaire, offered to students from 136 undergraduate courses on the 24 Unesp campuses. The partial results, which make up the sample, show the participation of 1,278 students. Of these, 66% (including health courses) had only theoretical classes, not in person and 18.8% had classes totally suspended. Of the sample participants, 69.4% considered their performance to be unsatisfactory during non-classroom classes. Compared to face-to-face classes, 68.3% of the students considered that their performance was inferior. As for learning, 78.4% had the perception that it was worse in relation to face-to-face classes. In addition, 83.2% of students stated that non-face-to-face classes are worse when compared to face-to-face classes, with preference (78.6%) for face-to-face classes. Regarding the students' perception, most had a predilection for on-site teaching, when compared to remote teaching, during the initial period of the pandemic. However, remote learning proved to be feasible, as it was the only alternative for the period.